Perlindungan Hukum Industri Kecil Menengah Batik Masaran Sragen - Djoko Kristianto; Dora Kusumastuti (STIE AUB Surakarta, 2018)
Batik Masaran Sragen regency is a batik industrial center that has great potential and has distinctive characteristics and is rich in both contemporary and modern motifs. However, from the potential of batik still has constraints and obstacles that are still found the low understanding of the importance of IPR protection both on copyright and brand rights, another constraint is the limited marketing is still using conventional models that do not have online media to reach the audience which is wider. The purpose of this community service activity is to conduct counseling and training on copyright and brand rights, as well as website creation training. The method used is through training, mentoring to partners and monitoring although community service activities have been completed to maintain the sustainability of the program. The impact of community service activities is that there has been a change of mindset about the importance of copyright and brand protection, as well as changes in marketing patterns from direct sales to sales through social media. Key Words : Copyrights Batik, Right Brand Batik, Marketing Batik